The Effect of the Project-Based Learning (PjBL) Model based on an Integrated STEM Approach with Entrepreneurial Character on Students' Creative Thinking Ability - Winda Ananda; Asni Johari; Nazarudin Nazarudin (Berkala Ilmiah Pendidikan Fisika, 2024)
This research aims to measure students' creative thinking abilities using the Project-Based Learning (PjBL) model based on an integrated STEM approach with entrepreneurial character in dynamic electrical material. This type of research is quasi-experimental with a none-equivalent pre-test and post-test control group design research model. The population in this study was all students in class XII phase F, with a total of 8 classes. The sampling was taken using cluster random sampling. Class F4 is an experimental class with 35 people, and class F3 is a control class with 35 people. The experimental class implemented STEM-based PjBL integrated entrepreneurial character and the control class with conventional learning. The instrument used was a 4 question description test to measure creative thinking. Based on the t-test, it was found that the initial abilities in both classes were the same in terms of creative thinking skills. The average post-test score for the experimental class and control class. Based on the t-test, there is a significant difference, which means there is an influence of STEM-based PjBL integrated with entrepreneurial character on creative thinking skills.